The impacts of sustainable industrial revolution (IR) on the profitability of Hungarian food companies - Máté, Domicián; Oláh, Judit; Erdei, Edina; Estiyanti, Ni Made; Bács, Zoltán; Kovács, Sándor (Frontiers in Sustainable Food Systems, 2022)
There is growing literature on the concept and objectives of sustainable development, but less attention is paid to a comprehensive approach to economic, social and environmental factors and technological change. The study identified a gap in research that addresses sustainability and Industrial Revolution (IR) concerns and allows for a holistic approach to assessing all three bottom-up dimensions. This study used quantitative path models to measure the extent to which Hungarian agri-food companies use IR factors in the three pillars of sustainable development. The research was conducted using partial least squares path modeling (PLS-PM) and categorical principal component analysis (CATPCA) to calculate the direct and indirect effects of sustainable IR factors on profitability outcomes. This study has shown that the livable and sustainable path hypotheses can be confirmed. However, sustainable IR's economic dimension directly impacts corporate returns significantly and positively. Decision-makers should not wait for a pie in the sky for emerging sustainability but consciously embrace the crucial environmental issues that only provide a direction for the necessary changes.